2022
DOI: 10.3961/jpmph.21.401
|View full text |Cite
|
Sign up to set email alerts
|

A Regionalization Model to Increase Equity of Access to Maternal and Neonatal Care Services in Iran

Abstract: Objectives: Access to maternal and neonatal care services (MNCS) is an important goal of health policy in developing countries. In this study, we proposed a 3-level hierarchical location-allocation model to maximize the coverage of MNCS providers in Iran.Methods: First, the necessary criteria for designing an MNCS network were explored. Birth data, including gestational age and birth weight, were collected from the data bank of the Iranian Maternal and Neonatal Network national registry based on 3 service leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These data consist of the demographic characteristics of the newborn's mother including gravidity and parity, medical history including previous miscarriage or abortion, risk factors, consanguinity of parents, gestational age and mode of delivery, date of birth, and pediatric data including baby's geographic location, gender, birth weight, presenting symptoms, diagnosis, neonatal complications, management, clinical outcome, and occurrence of perinatal death. 11,12 Greater than 97% of deliveries in Iran occur in hospitals, making the IMaN database a reliable sample of pregnancy and its complications throughout the country and an important source of epidemiological information for SARS-CoV-2 information in newborns. 11,12 Study patients included liveborn neonates 28 days of age having suspected as well as confirmed SARS-CoV-2 infection that were admitted to the hospital following delivery.…”
Section: Case Selection and Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…These data consist of the demographic characteristics of the newborn's mother including gravidity and parity, medical history including previous miscarriage or abortion, risk factors, consanguinity of parents, gestational age and mode of delivery, date of birth, and pediatric data including baby's geographic location, gender, birth weight, presenting symptoms, diagnosis, neonatal complications, management, clinical outcome, and occurrence of perinatal death. 11,12 Greater than 97% of deliveries in Iran occur in hospitals, making the IMaN database a reliable sample of pregnancy and its complications throughout the country and an important source of epidemiological information for SARS-CoV-2 information in newborns. 11,12 Study patients included liveborn neonates 28 days of age having suspected as well as confirmed SARS-CoV-2 infection that were admitted to the hospital following delivery.…”
Section: Case Selection and Inclusion Criteriamentioning
confidence: 99%
“…11,12 Greater than 97% of deliveries in Iran occur in hospitals, making the IMaN database a reliable sample of pregnancy and its complications throughout the country and an important source of epidemiological information for SARS-CoV-2 information in newborns. 11,12 Study patients included liveborn neonates 28 days of age having suspected as well as confirmed SARS-CoV-2 infection that were admitted to the hospital following delivery. Inclusion criteria for suspected cases included having a clinical presentation consistent with neonatal COVID-19 or those neonates having a positive history of contact with SARS-CoV-2-infected persons who required hospital admission.…”
Section: Case Selection and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…3 Meanwhile, every year an estimated 4 million of the 130 million babies born die in the neonatal period. 4 , 5 Most of these deaths occurred in low- and middle-income countries. 6 , 7 Most notably, maternal and neonatal disorders affect a large proportion of women and children in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Inequality and inability to access basic maternal healthcare services have been identified as the main causes of global mortality. 5 , 13 …”
Section: Introductionmentioning
confidence: 99%